Effects of High Volume Haemodiafiltration on Inflammatory Response Profile and Microcirculation in Patients with Septic Shock. (29th April 2015) - Tamme, Kadri; Maddison, Liivi; Kruusat, Rein; Ehrlich, Hans-Erik; Viirelaid, Mirjam; Kern, Hartmut; Starkopf, Joel
Abstract : Background . High volumes of haemofiltration are used in septic patients to control systemic inflammation and improve patient outcomes. We aimed to clarify if extended intermittent high volume online haemodiafiltration (HVHDF) influences patient haemodynamics and cytokines profile and/or has effect upon sublingual microcirculation in critically ill septic shock patients. Methods . Main haemodynamic and clinical variables and concentrations of cytokines were evaluated before and after HVHDF in 19 patients with septic shock requiring renal replacement therapy due to acute kidney injury. Sublingual microcirculation was assessed in 9 patients. Results . The mean (SD) time of HVHDF was 9.4 (1.8) hours. The median convective volume was 123 mL/kg/h. The mean (SD) dose of norepinephrine required to maintain mean arterial pressure at the target range of 70–80 mmHg decreased from 0.40 (0.43) μ g/kg/min to 0.28 (0.33) μ g/kg/min ( p = 0.009). No significant changes in the measured cytokines or microcirculatory parameters were observed before and after HVHDF. Conclusions . The single-centre study suggests that extended HVHDF results in decrease of norepinephrine requirement in patients with septic shock. Haemodynamic improvement was not associated with decrease in circulating cytokine levels, and sublingual microcirculation was well preserved.